2001
DOI: 10.1029/2001wr000371
|View full text |Cite
|
Sign up to set email alerts
|

Gaining and losing sections of horizontal wells

Abstract: Abstract. The flux along a horizontal well in uniform flow is examined using an analytic three-dimensional, steady model. Wells with uniform head and low pumping rates have gaining sections along which water enters the well and losing sections along which water exits. Such a well may provide a conduit for contaminated groundwater to be drawn into the well, conveyed a large distance, and injected into an uncontaminated region of an aquifer. Dimensionless ratios of the well's length L and radius R, aquifer thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Steward and Jin (2001) used an analytical model to examine losing sections of horizontal remediation wells (segments of the horizontal well where water flows out of the well and into the surrounding aquifer) in aquifers with uniform flow, and related the minimum pumping rate necessary to avoid losing sections to aquifer thickness, well length and radius. Steward and Jin (2001) used an analytical model to examine losing sections of horizontal remediation wells (segments of the horizontal well where water flows out of the well and into the surrounding aquifer) in aquifers with uniform flow, and related the minimum pumping rate necessary to avoid losing sections to aquifer thickness, well length and radius.…”
Section: Analytical and Numerical Solutions Of Flow Into Horizontal Wmentioning
confidence: 99%
“…Steward and Jin (2001) used an analytical model to examine losing sections of horizontal remediation wells (segments of the horizontal well where water flows out of the well and into the surrounding aquifer) in aquifers with uniform flow, and related the minimum pumping rate necessary to avoid losing sections to aquifer thickness, well length and radius. Steward and Jin (2001) used an analytical model to examine losing sections of horizontal remediation wells (segments of the horizontal well where water flows out of the well and into the surrounding aquifer) in aquifers with uniform flow, and related the minimum pumping rate necessary to avoid losing sections to aquifer thickness, well length and radius.…”
Section: Analytical and Numerical Solutions Of Flow Into Horizontal Wmentioning
confidence: 99%
“…One of those advantages is that a horizontal well can have a great length of screen, thus can withdraw a significant amount of groundwater. In recent years, horizontal wells have gained increasing interests in the field of water resources management and environmental engineering, and a great deal of research can be found from Morgan (1992); Tarshish (1992); Cleveland (1994); Murdoch (1994); Falta (1995); Sawyer and Lieuallen-Dulam (1998); Zhan (1999); Zhan and Cao (2000); Streward and Jin (2001); Zhan et al (2001); Zhan (2002, 2003); Zhan and Zlotnik (2002); Chen et al (2003); Zhan and Park (2003), and others.…”
Section: Introductionmentioning
confidence: 99%
“…The analytic element method uses the superposition of appropriate potential functions and applied normally to the case of an aquifer of an infinite extent [126]. The analytic element method can be used to determine the shape of capture zone due to pumping for problems of 3-D flow induced by horizontal flow [255,256]. In capture zone delineation, this methods may be used with other approaches such as the locations of stagnation points in a flow field to describe the streamline [311] or the separation of variables and theory for multi-aquifer flow [312].…”
Section: Methodsmentioning
confidence: 99%
“…Steward [254] first built a 3-D steady-state groundwater flow model using the analytic element method to delineate a capture zone caused by a horizontal well in a contaminated site in an infinite aquifer. The model was then used to quantify the losing sections where water exits through the horizontal well [255], to model the drawdown and capture zone topology for nonvertical wells [256], and to examine the impact of well design on the head distribution with a horizontal well [257].…”
Section: Methodsmentioning
confidence: 99%